Coastal reservoirs in China - Lin,Pengzhi (IAHR, 2020)
Modern river basin management treats flooding not only as a threat, but also as a precious water resource. In inland areas, dams are built to impound water in reservoirs. In coastal regions, however, building reservoirs does not seem to be an obvious choice, at least at first glance. How to develop more freshwater for coastal cities becomes a challenging issue. For coastal regions with abundant precipitation and/or river outflow, the key to solving water shortage problem is to find a suitable place to store freshwater, especially during the flood season.